Linfogranuloma venéreo: 160 anos de progressos clínicos e laboratoriais - Neves, René Garrido; Santos, Omar Lupi da Rosa (Brazilian Journal of Sexually Transmitted Diseases, 1996)
Lymphogranuloma venercum (LGY) is an acute to chronic sexually transmitted infectious disease with transient genital lesions followcd by significant regional lymphadenopathy as well as systemic manifestations. LGV may progrcss to late fibrosis and tissue destruction in untreated cases. The causative organism is Chlamydia trachomaris. It is more frequent in tropical and subtropical climates, in areas of low socioeconomic development or great sexual promiscuity.